Класифікаційні засади вивчення граматичних категорій - Костусяк, Наталія Миколаївна; Kostusyak, N. M. (Житомирський державний університет імені Івана Франка, 2012)
У статті комплексно досліджено граматичні категорії української мови; проаналізовано стан опрацювання та основні напрями дослідження цієї проблеми на сучасному етапі; описано систему класифікаційних ознак, що лежать в основі виокремлення аналізованих мовних явищ; указано на двобічність граматичних категорій (наявність змістових і формальних ознак); зазначені одиниці розглянуто відповідно до рівневої організації мовної системи; простежено особливості категорійної системи на тлі частиномовної належності слів. In the article a comprehensive study of grammatical categories of the Ukrainian language is carried out, the state of development and the main directions of research on this problem at the present stage are analyzed, the system of classification features that underlie the selection of the analyzed linguistic phenomena is described ; in two sides of grammatical categories (presence of content and formal features) is specified ; these units according to the level of language system are considered; categorical features against a background of association with parts of speech are traced, specifically as a noun and a verb most clearly in terms of categorical specialization of lexical and grammatical classes of words are mentioned, the derivational relationship between the grammatical categories non-derivative and derivative categories is delineated.
Classification foundations for the study of grammatical categories
Keywords: граматична категорія; морфологічна категорія; синтаксична категорія; словотвірна категорія; grammatical category; morphological category; syntactic category; derivational category; 811.161.2’366.5